A Novel Protein Hydrolysate-Based Biostimulant Improves Tomato Performances under Drought Stress - Silvana Francesca; Valerio Cirillo; Giampaolo Raimondi; Albino Maggio; Amalia Barone; Maria Manuela Rigano (Plants, 2021)
Abiotic stresses adversely affect crop production causing yield reductions in important crops, including tomato (Solanum lycopersicum L.). Among the different abiotic stresses, drought is considered to be the most critical one, since limited water availability negatively impacts plant growth and development, especially in arid and semi-arid areas. The aim of this study was to understand how biostimulants may interact with critical physiological response mechanisms in tomato under limited water availability and to define strategies to improve tomato performances under drought stress. We investigated the physiological responses of the tomato genotype ‘E42’ grown in open fields under optimal conditions (100% irrigation) and limited water availability (50% irrigation) treated or not with a novel protein hydrolysate-based biostimulant (CycoFlow, Agriges, BN, Italy). Plants treated with the protein hydrolysate showed a better water status and pollen viability, which also resulted in higher yield under drought stress compared to untreated plants. The treatment with the biostimulant had also an effect on antioxidant contents and activity in leaves and fruits depending on the level of irrigation provided. Altogether, these results indicate that the application of protein hydrolysates on tomato improved plant performances under limited water availability and in different experimental fields.